2018
DOI: 10.1002/agm2.12031
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the MRI‐based Brain Atrophy and Lesion Index in the evaluation of whole‐brain structural health

Abstract: BackgroundThe Brain Atrophy and Lesion Index (BALI), which evaluates several common aging‐related MRI changes in combination, has been validated as a feasible method to assess the status of structural brain health. Previous studies have been based primarily on older participants and high‐field MRI. Here, we tested the generalizability of the BALI by examining its measurement properties in a wide age range at both high and conventional MRI field strengths.MethodsSubjects (n = 229) who had T2WI at either 1.5T or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Given that DICOM is the default format with all MRI scanners, brain scans can be readily evaluated without the need for reformatting. Despite these limitations, in this study, the evaluation of BALI strictly followed standard procedures (Guo et al, 2014a) and, as demonstrated elsewhere, the resulting BALI scores showed great intra-rater and inter-rater reliability (Gu et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Given that DICOM is the default format with all MRI scanners, brain scans can be readily evaluated without the need for reformatting. Despite these limitations, in this study, the evaluation of BALI strictly followed standard procedures (Guo et al, 2014a) and, as demonstrated elsewhere, the resulting BALI scores showed great intra-rater and inter-rater reliability (Gu et al, 2018).…”
Section: Discussionmentioning
confidence: 68%
“…Given that high field strength can allow high signal-to-noise ratios and greater image contrast, it is not surprising that a significantly higher mean BALI total scores using 3.0T over 1.5T images (6.84 ± 3.28 vs.5.80 ± 2.92, t = 2.17, p = 0.031). On the other hand, the evaluation has been proven reliable (Gu et al, 2018) and data collection was not biased for field-strength, in terms of age and possession of the risk factors under study (e.g., mean age 48.77 ± 12.87 vs. 47.00 ± 11.41, t = 0.94, p = 0.348; mean number of risk factors 1.93 ± 1.18 vs. 1.78 ± 1.24, t = 0.85, p = 0.398). Previous studies have also demonstrated the reliability and comparability of both field strengths (Guo et al, 2014b; Gu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation